PERSEPSI TOP EXECUTIVE (SEKTOR PUBLIK DAN SWASTA) TERHADAP FUNGSI INTERNAL AUDIT - Hery . (Media Riset Akuntansi, Auditing & Informasi, 2004)
The Main purpose of this research is to find out: (1) on how the Top Executive give their perception against the function of internal audit, and (2) on differences, if any, between perception of public Top Executive and private Top Executive against internal audit.The method that is used to Collect data was based on survey method and convenience sampling. Primary data was taken from closed questionnaire, taken from 73 Top Executive, which consist of 41 Top Executive of public sector (BUMN) and 32 Top Executive of private sector. The Scale measurement using the method of Likert's scale on five points. Data then was analysed statistically (quantitative) by used Z observation and t-test to prove the truth of hypothesis .The result of analysis shows that any Top Executive have negative perception about internal audit and no significant difference between public Top Executive and private Top Executive about perception toward the function of internal audit, whether from aspects 'watchdog', audit tee performance, preventive, intemal consultant, or knowledge.Keywords: Internal audit, perception, public & private top executive